1995
DOI: 10.1017/s0017089500030445
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of orthogonal polynomials satisfying fourth order differential equations

Abstract: Introduction.In the last few years, there has been considerable interest in the properties of orthogonal polynomials satisfying differential equations (DE) of order greater than two, their connection to singular boundary value problems, their generalizations, and their classification as solutions of second order DE (see for instance [2-8]). In this last interesting problem, some known facts about the classical orthogonal polynomials can be incorporated to connect these two sets of families and yield some nontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…One direction of the statement (zeros of a polynomial solutions satisfy the system of equations) is a fairly straightforward computation and the outline of the argument can be found, for example, in [8] or, as a remark, in [11, §3]. Moreover, results in this direction can be obtained for much more general differential equations of higher order (see, for example, [4,5,6]). Arguments in the other direction seem to exist only in special cases, as in the work of Stieltjes, and are based on interpreting the system of equations as the critical point of an associated energy functional (see e.g.…”
Section: 2mentioning
confidence: 99%
“…One direction of the statement (zeros of a polynomial solutions satisfy the system of equations) is a fairly straightforward computation and the outline of the argument can be found, for example, in [8] or, as a remark, in [11, §3]. Moreover, results in this direction can be obtained for much more general differential equations of higher order (see, for example, [4,5,6]). Arguments in the other direction seem to exist only in special cases, as in the work of Stieltjes, and are based on interpreting the system of equations as the critical point of an associated energy functional (see e.g.…”
Section: 2mentioning
confidence: 99%
“…The first is the electrostatic interpretation of the zeros of polynomials satisfying second order differential equations [15]- [17], the second is a simple curve fitting of numerical data and the third is the known fact that the points of well-defined curves in the complex plane are limit points of the zeros of the normalized Bessel polynomials [8]- [11]. The formulas yielded by the electrostatic interpretation of the zeros of Bessel polynomials are used to find them numerically as it has been done previously with these and other sets of points [7]- [19]. Several sets of zeros are computed in this way and the sets of real and imaginary values are fitted by polynomials depending on the index k whose coefficients depend on n. Finally, it is found that the approximate expression for the kth zero of y n (x) is O(1/n 2 )-convergent to a limit point of the zeros of the Bessel polynomials.…”
Section: Introductionmentioning
confidence: 99%